Can I solve my structure by SAD phasing? Anomalous signal in SAD phasing - Terwilliger, Thomas C. (International Union of Crystallography, 2016)
The useful anomalous correlation and the anomalous signal in a SAD experiment are metrics describing the accuracy of the data and the total information content in a SAD data set and are shown to be related to the probability of solving the anomalous substructure and the quality of the initial phases.